Experimental Evaluation of Evaporative Cooling for Enhancing Photovoltaic Panels Efficiency Using Underground Water - Arwa M. Kadhim; Issam Mohamed Ali Aljubury (Journal of Engineering, 2020)
This paper presents an experimental study of cooling photovoltaic (PV) panels using evaporative cooling. Underground (geothermal energy) water used to extract heat from it during cooling and cleaning of PV panels. An experimental test rig was constructed and tested under hot and dusty climate conditions in Baghdad. An active cooling system was used with auxiliary an underground water tank to provide cold water as a coolant over both PV surfaces to reduce its temperature. The cellulose pad has been arranged on the back surface and sprays cooling on the front side. Two identical PV panels modules used: without cooling and evaporative water cooling. The experiments are comprised of four cases: Case (I): backside cooling, Case (II): front and back cooling (pump supply water every 35 minutes), Case (III): cooling both sides using Arduino controller. Water cooling pump operation depending on the panel temperatures (temperature sensors were installed on the front of the panel), Case (IV): Repeating case III with different water flow rates. Experimental results showed that the average reduction in module temperatures was 4, 8,12.2 and 12.6 ⁰C respectively by Case (I), (II), (III) and (IV) with respect to a non-cooling module. Using evaporative water cooling achieved a total improvement of 1.74%, 2.8%, 15.8%, and 16% in the conversion efficiency of the panel by the Case (I), (II), (III) and (IV) respectively when compared to a non-cooling module.